An easily fabricated nano-hydroxyapatite modified glassy carbon electrode for the degradation of methylene blue. (14th January 2022) - Han, Di; Qian, Gongming; Ye, Qing; Feng, Mingjia
Abstract : According to the existing photocatalytic properties and adsorption properties of hydroxyapatite, the electrochemical properties of hydroxyapatite have been studied to provide ideas for the design of new mineral electrocatalysts. Abstract : The exploitation of efficient electrocatalysts is very important for the degradation of refractory organic pollutants. In this paper, we demonstrated for the first time that nano-HAP (nHAP) has good performance and strong stability in the electrocatalytic degradation of organic pollutants and can be used as a potential electrode material. The mineral electrode was prepared quickly and cheaply by drip-coating nHAP powder on a glassy carbon electrode (GCE) for electrocatalytic degradation of methylene blue (MB). Morphological characterization has been performed with SEM and AFM. The electrochemical behaviour was investigated using cyclic voltammetry and Tafel curves. The degradation ratio of MB by the nHAP-modified electrode was 81.03%, which is 1.5 times that by the bare GCE in 0.5 mg L −1 MB solution. Therefore, HAP is a new mineral electrode with low production cost, high catalytic efficiency and long service life.